Prevalence of hypertension among internally displaced persons and host community members in conflict-affected areas of Southern Kaduna, Nigeria: A community-based comparative cross-sectional study - Ali Babangida; Alheri Kazum Dowoh (Public Health – Open Journal, 2026)
Hypertension is a leading cause of morbidity and mortality in Nigeria, with conflict-affected populations facing disproportionately higher risks due to displacement-related stressors and healthcare disruptions. However, the burden of hypertension in the chronically unstable region of Southern Kaduna remains unquantified. This study aimed to determine the prevalence of hypertension and assess the cascade of care among internally displaced persons (IDPs) and host community members in this setting. Methods: We conducted a community-based comparative cross-sectional study from March to June 2025 in three conflict-affected Local Government Areas (Kachia, Kajuru, and Chukun) of Southern Kaduna, Nigeria. A multi-stage sampling technique was used to enroll 1,148 adults (574 IDPs, 574 hosts). Data were collected using validated questionnaires (WHO STEPS, PSS-4) and standardized anthropometric and blood pressure measurements. Hypertension was defined as systolic BP ≥140 mmHg and/or diastolic BP ≥90 mmHg, or self-reported use of antihypertensive medication. We compared prevalence, awareness, treatment, and control between IDPs and hosts using chi-square tests. Findings: The overall hypertension prevalence was 36.8% (95% CI: 34.0–39.6%). Prevalence was significantly higher among IDPs (42.3%; 95% CI: 38.3–46.5%) than among host community members (31.2%; 95% CI: 27.5–35.1%), an absolute difference of 11.1 percentage points (p<0.001). Nearly half (46.1%) of hypertensive IDPs were diagnosed for the first time during the survey, compared to 36.9% of hosts (p=0.032). The care cascade for hypertensive IDPs revealed profound attrition: only 53.9% were aware of their diagnosis, 35.4% were on treatment, and a mere 12.8% achieved blood pressure control. These figures were significantly worse than those for the host community (69.3% aware, 54.7% treated, 26.3% controlled; p<0.01 for all). Conclusion: This study provides the first empirical evidence that internally displaced persons in Southern Kaduna bear a substantially higher and largely uncontrolled burden of hypertension compared to their host communities. The near-complete failure of the care cascade—where 87 of every 100 hypertensive IDPs live without control—represents a critical failure of the health system and a form of structural violence. These findings demand the urgent integration of non-communicable disease care into humanitarian responses in Nigeria’s conflict zones.